The Influence Of Burnout And Emotional Intelligence On Job Satisfaction With Job Stress As Mediation At Pratama Isykarima Clinic Cikarang - Siti Latifah; Preatmi Nurastuti; Billy Josef Anis (UNIVED Press, 2024)
This study aims to determine The Influence Of Burnout And Emotional Intelligence On Job Satisfaction With Job Stress As Mediation At Pratama Isykarima Clinic Cikarang. Respondents of this study were 57 respondents and this study used a quantitative approach with the SmartPLS 3.0 data processing application. The results of this study found that 1. Burnout affects Job Satisfaction, 2. Emotional Intelligence has no effect on Job Satisfaction, 3. Job Stress has no effect on Job, 4. Burnout affects Job Stress, 5. Emotional Intelligence affects Job Stress, 6. Job Stress as a mediating variable has a role in weakening the effect of Burnout on Job Satisfaction, 7. Job Stress as a mediating variable has a role in weakening the effect of Emotional Intelligence on Job Satisfaction.